Antimicrobial Resistance Dynamics in the Chicken Gut after Amoxicillin and Thiamphenicol Treatments. (March 2022) - Laconi, A.; Tolosi, R.; Cuccato, M.; Gras, L. Mughini; Cannizzo, F.T.; Tilli, G.; Piccirillo, A.
Abstract : Purpose: the aim of the study was to investigate the selective pressure exerted by amoxicillin (beta-lactam) and thiamphenicol (phenicol) administration on the abundance of antimicrobial resistance genes (ARGs) in the chicken gut. Methods & Materials: eighteen broiler chicks were allocated in three groups and reared without treatment or treated with either amoxicillin or thiamphenicol at 5 days of age for three consecutive days. Cloacal swabs were taken from all birds at 1 day of age, as reference, and then on days 8, 19, and 28. At the end of the rearing cycle, birds were slaughtered and the caecal content was aseptically collected. Swabs (n = 72) and caecal contents (n = 13) were analysed by quantitative PCR assays to generate data on the abundance of fourteen ARGs conferring resistance to beta-lactams (n = 8) and phenicols (n = 6). Difference in ARGs abundance over time points within the same group was assessed using Friedmann test with Dunn's test for multiple comparisons, while Spearmann's rank correlation was used to assess the co-occurrence of beta-lactam and phenicol ARGs. Results: increased abundance of ARGs conferring resistance to phenicols was observed in the groups treated with either amoxicillin or thiamphenicol (p < 0.05). In detail, the abundance of floR and cmlA genes was significantly increased (p < 0.05) after treatment with either of the two antimicrobials up to 21 days post-treatment (d.p.t.). Amoxicillin treatment enhanced the abundance of bla SHV at 1 d.p.t. (p < 0.05). Positive correlations between bla TEM-1 and floR (p < 0.05; r = 0.245) and cmlA (p < 0.0001; r = 0.325) were also observed. Conclusion: the results of the study seem to suggest an increasing trend of abundance of bla TEM-1, conferring resistance to beta-lactams, and cmlA and floR, conferring resistance to phenicols, under the selective pressure exerted by amoxicillin and phenicols.